PENGARUH TOTAL ASSET TURNOVER DAN NET PROFIT MARGIN TERHADAP PERTUMBUHAN LABA PADA PT BISI INTERNASIOAL TBK PERIODE 2014-2024 - Melani Ditha Safitri; Eka Rahim (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of Total Asset Turnover (TATO) and Net Profit Margin (NPM) on Profit Growth at PT BISI Internasional Tbk for the period 2014-2024. The research method uses a quantitative approach with an associative nature, which includes a causal relationship between independent and dependent variables. The analytical techniques used include descriptive statistics, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²). The results of the study show that, partially, TATO has a significant effect on profit growth (t-count -6.064 < t-table 2.306; significance 0.000 < 0.05), while NPM also has a significant effect on profit growth (t-count 4.072 > t-table 2.306; significance 0.004 < 0.05). Simultaneously, TATO and NPM have a significant effect on profit growth (F-count 26.658 > F-table 4.459; significance 0.000 < 0.05). The coefficient of determination (R²) value of 87.0% indicates that TATO and NPM explain 87.0% of the variation in profit growth, while the remaining 13.0% is influenced by other factors outside the model.